Evaluation of the dual-feed rotor spinning unit based on airflow dynamics and blended yarn properties. Issue 11 (2nd November 2017) - Akankwasa, Nicholus Tayari; Lin, Huiting; Wang, Jun
Abstract: In fiber processing on a rotor spinning machine, the fiber orientation gained in pre-processing stages like carding and drawing is mainly lost as the fibers enter the rotor interior for further processing. To improve fiber orientation and facilitate fiber blending, a new dual-feed rotor spinning unit is proposed. We present a comprehensive numerical evaluation of the airflow dynamics in the original and the proposed rotor spinning unit based on finite volume methods. The velocity profiles, pressure distribution, vortices, streamlines, and drag force in the two prototypes are evaluated. Results reveal that the velocity magnitude and pressure in the dual-feed unit adopt an even pattern and the total drag force reduction of up to 60–80% is achieved. Comparison of the yarn quality properties of the two systems showed that the dual-feed spun yarns possess superior quality compared to the conventional yarns.